The Research on Intelligent Seating Position Type LED Table Lamp - Ling Liu; Qi Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Taking STC89C52RC single-chip as control core, this research realizes intelligent control function, which can automatically detect whether there is someone in the room and turn on/off LED table lamp; brightness of LED lamp can be adjusted with manual mode. In addition to that, it also has other functions such as displaying time and date, and posture correction. In general, time, data and brightness can be regulated through key module. 8 high brightness white LED are used in illumination module, among which, light sensitive module is applied for testing luminous intensity of environment; ultrasonic distance measuring module is utilized for detecting the distance from men to table lamp through transmitting and receiving ultrasound. In the evening, light is on when the distance from men to table lamp is within certain range; and light is off when exceeding this range. However, if the distance is lower than the specified minimum distance, buzzer will alarm to warn user that the seating position needs to be corrected. C language programming is employed for the integrated software to achieve the overall control function.